A study on the impact of relationship strength in technological collaboration networks, absorptive capacity, and leadership regulatory focus on team ambidextrous innovation - LI, Zhen (Institutional Knowledge at Singapore Management University, 2024)
In the context of rapid global economic development, competition among enterprises has become increasingly fierce, making innovation the core driving force for maintaining competitive advantage and promoting sustainable development. This paper explores the impact of relationship strength within technological collaboration networks, absorptive capacity, and leadership regulatory focus on incremental and radical innovation. The study finds that while relationship strength has no significant impact on incremental innovation, it has a negative effect on radical innovation. The absorptive capacity within technological collaboration networks positively influences both types of innovation. The research also highlights the critical role of leadership regulatory focus: High prevention-focus leaders are more inclined to promote incremental innovation, whereas those with a high promotion focus are more likely to drive radical innovation. Leadership style positively influences the direction of team innovation and positively moderates the effects of relationship strength and absorptive capacity on innovation. Based on these findings, the paper suggests that enterprises should balance relationship strength when building technological collaboration networks, leveraging weak ties’ novel information and perspectives to foster radical innovation. Furthermore, companies should continuously enhance their absorptive capacity, strengthen the internal flow and integration of knowledge, and ensure the effectiveness of innovation activities. Additionally, enterprises should adjust leadership styles according to the needs of their innovation strategies to accommodate different types of innovation. This study not only enriches the theoretical understanding of the influence of technological collaboration, absorptive capacity, and leadership regulatory focus on innovation but also provides practical guidance on adjusting organisational and management strategies to meet different innovation demands. Future research could further explore how these factors interact to influence innovation outcomes in different cultural and industrial contexts.